Fracture Characteristics of Deep Shale Gas Reservoirs and Their Relationship with Tectonic Evolution Based on Electric Imaging Logging - ZHANG Xuanang; YAN Jianping; LIAO Maojie; ZHONG Guanghai; GUO Wei; HUANG Yi (Cejing jishu)
In order to find out the relationship between fractures and tectonic evolution in deep shale gas reservoirs, this paper makes full use of electric imaging logging data, core and geochemical data to study the types, occurrence characteristics, formation periods and the relationship between structural evolution and structural fracture in deep shale gas reservoir of L20X well in Luzhou, south Sichuan. The results show that, first the structural fractures can be divided into cross-layer shear fractures, intra-layer tension fractures, bedding detachment fractures, composite fractures, and structural pressure-soluble suture lines. The structural joints that can be identified by electric imaging logging data are high resistance joints, high guide joints and fault joints, and the high resistance joints and high guide joints are mostly through-layer shear joints. Second, the formation of tectonic fractures is mainly influenced by three phases of tectonic movement: during the Indochinese period, the shear fractures in the NEE section and the faults in the NWW section developed due to the NNW stress compression. The NNE shear fractures and NEE faults were developed in the late and early mountains of Yanshan due to SEE compression. Due to NEE compression, NW shear fractures and NNE faults developed in the middle and late mountains. The fracture strike occurrence of NEE, NNE, NW, which is closely related to the third-stage tectonic movement, is the structural record left by the third-stage tectonic movement in the stratum. This study indicates that the electric imaging logging data provide basis for the analysis of the sub-evolution of the tectonic period.